FAKTOR-FAKTOR PENDORONG RESIDIVISME TINDAK PIDANA NARKOBA - Christian Situmorang; Padmono Wibowo (Causa: Jurnal Hukum dan Kewarganegaraan, 2023)
Residivism in drug-related crimes remains a critical issue, impacting the rehabilitation process and reintegration of former inmates into society. This study focuses on Lembaga Pemasyarakatan in South Sulawesi, Indonesia, to explore the factors driving recidivism among drug offenders. Through a comprehensive analysis of internal and external factors, including individual characteristics, social environment, and social control, this research aims to identify the root causes of recidivism in drug-related crimes. The study also highlights the practical challenges faced by the institution, such as limited facilities, financial constraints, and the need for effective post-release supervision. To address these issues, practical recommendations include enhancing facilities, implementing structured rehabilitation programs, fostering collaboration with NGOs and local communities, and increasing family education. On a theoretical level, this research calls for further studies, the development of specific theoretical models, program evaluation, and comparative research to identify best practices in tackling drug-related crime recidivism. This study aims to contribute to the effective prevention and rehabilitation of drug offenders, ultimately reducing recidivism rates and facilitating their positive reintegration into society.